Building a Knowledge-Based Economy in Bangladesh - Qamruzzaman, Md.; Ferdaous, Jannatul (Asian Business Review, 2014)
The concept of “knowledge economy” is based on the view knowledge and information are at the center of economic growth and development. In today´s ever changing world knowledge has become a key element for sustainable economic development. This study aims to identify key challenges for developing knowledge based economy in Bangladesh. Study results revealed that key challenges faced by Bangladesh are reluctant of economic sectors to become accustomed IT based operation rather than traditional practice and lack of skilled manpower. To overcome those challenges concerted efforts are imperative by implementing a comprehensive strategy based on research and sound economic principles, help use of ICT in businesses and Government sector and Investment in human capital. JEL codes: R120, D 830